Biruloquinone, an Acetylcholinesterase Inhibitor Produced by Lichen-Forming Fungus Cladonia macilenta - Luo, H., Jiangsu University of Science and Technology, Zhenjiang, China; Li, C.T., Jilin Agricultural University, Changchun, China; kim, J.C., Korea Research Institute of Chemical Technology, Daejeon, Republic of Korea; Liu, Y.P., Jiangsu University of Science and Technology, Zhenjiang, China; Jung, J.S., Sunchon National University, Sunchon, Republic of Korea; Koh, Y.J., Sunchon National University, Sunchon, Republic of Korea; Hur, J.S., Sunchon National University, Sunchon, Republic of Korea (Journal of microbiology and biotechnology, 2013)
At present, acetylcholinesterase (AChE) inhibitors are the first group of drugs to treat mild to moderate Alzheimers disease (AD). Although beneficial in improving cognitive and behavioral symptoms, the effectiveness of AChE inhibitors has been questioned since they do not delay or prevent neurodegeneration in AD patients. Therefore, in the present study, in order to develop new and effective anti-AD agents from lichen products, both the AChE inhibitory and the neuroprotective effects were evaluated. The AChE inhibitory assay was performed based on Ellman’s reaction, and the neuroprotective effect was evaluated by using the MTT method on injured PC12 cells. One AChE inhibitor (IC50 = 27.1 μg/ml) was isolated by means of bioactivity-guided isolation from the extract of lichen-forming fungus Cladonia macilenta, which showed the most potent AChE inhibitory activity in previous screening experiment. It was then identified as biruloquinone by MS, and 1H- and 13C-NMR analyses. The inhibitory kinetic assay suggested that biruloquinone is a mixed-II inhibitor on AChE. Meanwhile, biruloquinone improved the viability of the H2O2- and β-amyloid-injured PC12 cells at 1 to 25 mg/ml. The protective effects are proposed to be related to the potent antioxidant activities of biruloquinone. These results imply that biruloquinone has the potential to be developed as a multifunctional anti- AD agent.